Dopaminergic agents in the treatment of bipolar depression: a systematic review and meta‐analysis. (3rd March 2017) - Szmulewicz, A. G.; Angriman, F.; Samamé, C.; Ferraris, A.; Vigo, D.; Strejilevich, S. A.
Abstract : Objective: To systematically examine the effects of dopaminergic agents (modafinil, armodafinil, pramipexole, methylphenidate, and amphetamines) on bipolar depression outcomes. Methods: Meta‐analysis of randomized controlled trials was performed to assess the efficacy and safety of treatment with dopaminergic agents in bipolar depression. In a secondary analysis, findings from both randomized controlled trials and high‐quality observational studies were pooled by means of meta‐analytic procedures to explore dopaminergic treatment‐related new mania. Results: Nine studies (1716 patients) were included in our meta‐analysis of randomized controlled trials. Treatment with dopaminergic agents for bipolar depression was associated with an increase in both response (1671 individuals, RR 1.25, 95% CI 1.05 to 1.50) and remission rates (1671 individuals, RR 1.40, 95% CI 1.14, 1.71). There was no evidence of an increased risk of mood switch associated with this treatment (1646 individuals, RR 0.96, 95% CI 0.49, 1.89). Our secondary analysis (1231 individuals) yielded a cumulative incidence of mood switch of 3% (95% CI 1.0, 5.0) during a mean follow‐up period of 7.5 months. Conclusions: Preliminary findings suggest that dopaminergic agents may represent a useful alternative for the treatment of bipolar depression, with no evidence for a related increase in the risk of mood destabilization during short‐term follow‐up.